Strategic Optimization of Student Management in Strengthening the Institutional Image of Educational Institutions: A Multi-Case Study at the Junior Secondary School Level - Evi Fatus Zahra; Abdullah Abdullah (Universitas Nurul Jadid, 2024)
This study aims to analyze the optimization of student management in improving the branding image of schools through a multi-case study at SMP Negeri 1 Mlandingan and SMP Negeri 2 Mlandingan. Student management plays a strategic role in supporting educational quality and strengthening public trust in educational institutions. This research employed a qualitative approach using a multi-case study design. Data were collected through in-depth interviews, observations, and documentation involving school principals, vice principals, teachers, students, and parents. The data were analyzed through data reduction, data display, and conclusion drawing, while validity was ensured through source and technique triangulation. The findings reveal that the optimization of student management is implemented through systematic planning, student admission management, student development programs, discipline enforcement, extracurricular activities, academic and non-academic achievement enhancement, and continuous monitoring and evaluation. These efforts contribute significantly to building a positive school image characterized by improved student achievements, increased community trust, stronger stakeholder engagement, and higher enrollment rates. Furthermore, both schools integrate student-centered management practices with institutional vision and mission to create a competitive and distinctive branding image.